2014
DOI: 10.4067/s0717-95022014000200011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Occipital Condyle and Comparison of its Dimensions with Head and Foramen Magnum Circumferences in Dry Skulls of Iran

Abstract: SUMMARY:The occipital condyle (OC) is an important area in craniovertebral surgery, but its anatomical features and the procedures concerning the OC have not been studied in detail yet. The aim of this study was to revisit the anatomy of the occipital condyle region and assess variations of the surrounding structures. Observations, on fifty dry skulls (dried specimens, 100 sides) and determined of condyle measurements. The mean length, width and height of occipital condyle were found to be 19.43±3.27 (right), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 11 publications
3
18
3
Order By: Relevance
“…In a study by Bayat et al [1], the mean length of left occipital condyle was 19.28 mm and right occipital condyle was 19.43 mm. These findings were observed lesser than our present study findings.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In a study by Bayat et al [1], the mean length of left occipital condyle was 19.28 mm and right occipital condyle was 19.43 mm. These findings were observed lesser than our present study findings.…”
Section: Discussionmentioning
confidence: 92%
“…near the foramen magnum will be the dorsal approach [1]. Different procedures are adapted by the neurosurgeons to minimise the morbidity like lateral, transcondylar approach [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study observed that for both males and females, the left and right OC length and MxOC width were significantly different; with the left being greater than the right, However the MnOC width was bilateral. Asymmetry in OC dimensions has been reported by Agnihotriet al (2014), [20] and Bazyatet al (2014), [18] in which they stated that the right OC parameters had mean values significantly greater than the left; however, Lang (1995), [33] Cicekcibasiet al (2004), [8] and Tale et al's (2016), [34] reported no significant bilateral differences in the condyle parameters. The hypothesis of difference in data acquisition (radiologic, osteometric and photogrammetric) report by Lang and Hornung (1993), [23] inconsistencies in collection methods (Bozbugaet al, 1999), [15] and genetic endowment (Le et al, 2011;Yu et al, 2015); [13,14] as well as racial/ethnic differences (Lang and Hornung, 1993;Lang, 1995;Bozbugaet al, 1999;Cicekcibasiet al, 2004), [8,15,23] are undoubtedly factors which could impact on the range differences in the value obtained in morphometric studies.…”
Section: Resultsmentioning
confidence: 78%
“…[5][6][7][8] The occipital condyle (OC) and basilar process (BP) are structures located at the skull base which forms part of the floor of the cranial cavity which by location, differentiates the brain from facial structures and suprahyoid neck (Rautet al, 2012). [9] Name & Address of Corresponding Author Aigbogun (Jr) [8,13,14] with higher values reported for the Asians (Bozbugaet al, 1999; Yu et al, 2015; Salujaet al, 2016), [14][15][16] and lower values for the Caucasians and Australians (Wen et al 1997;Bazyatet al, 2014), [17,18] while for Africans the values fall between values of Asians and Caucasians (Salihet al, 2014; Agnihotriet al, 2014). [19,20] Only a few studies have reported morphometric values for the basilar process (clivus), with dimensions ranging from 24mm to 27mm (Oliviera, 1975; Wescott and Moore-Jansen, 2001), [21,22] and higher values for whites when compared to blacks (Wescott and Moore-Jansen, 2001).…”
Section: Introductionmentioning
confidence: 99%